2016
DOI: 10.1016/j.rmed.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an oral anti-oxidant, N-Acetyl-cysteine, on inflammatory and oxidative markers in pulmonary sarcoidosis

Abstract: Oral NAC increased GSH levels but failed to suppress in-vivo TNF-α production in contrast to effects in-vitro. Anti-oxidant therapy may still play a role in the management of sarcoidosis but therapy with better bioavailability or potency is needed to suppress the lung inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As a mucolytic agent, NAC not only has the effect of directly dissolving mucus expectorant but also has the effect of anti-inflammatory, antioxidant, increasing the secretion and activity of active substances in the lung. [ 12 15 ] A large number of free radicals are produced in ARDS patients. Endogenous antioxidant substances may reduce the damage to target cells, lung interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a mucolytic agent, NAC not only has the effect of directly dissolving mucus expectorant but also has the effect of anti-inflammatory, antioxidant, increasing the secretion and activity of active substances in the lung. [ 12 15 ] A large number of free radicals are produced in ARDS patients. Endogenous antioxidant substances may reduce the damage to target cells, lung interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a mucolytic agent, NAC not only has the effect of directly dissolving mucus expectorant but also has the effect of anti-in ammatory, antioxidant, increasing the secretion and activity of active substances in the lung (12)(13)(14)(15). A large number of free radicals are produced in ARDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that NAC failed to suppress ex vivo TNF-α production from BAL cells despite effects in vitro, a discrepancy that the authors attributed to the poor pulmonary bioavailability of oral NAC in the lung tissue. Conversely, there was a 59% increase in BAL GSH levels after NAC treatment, an encouraging result that can still support the idea that antioxidant therapy may have a role in the management of sarcoidosis, although no clinical trials have yet followed up these findings [ 106 ].…”
Section: Antioxidant Interventions In Sarcoidosismentioning
confidence: 99%